MODEL OF CRIMINAL CASE RESOLUTION OF TRAFFIC ACCIDENTS CAUSING DEATH - Ismunarno, Ismunarno; Rofikah, Rofikah; Slamet, Sabar (Faculty of Law, Universitas Sebelas Maret, 2017)
The present research seeks to find out a model of criminal case resolution of traffic accidents causing death in Traffic Directorate of Yogyakarta (DIY) Police Department through either criminal justice system or mediation. Socio-legal research or non-doctrinal research has been used for this research. The research location is located in the Traffic Directorate of Yogyakarta Police Department. The research data use primary and secondary data. The results of this research indicate that in Traffic Directorate of DIY Police Department criminal case of traffic accidents causing death is resolved through criminal justice system with a record of ordinary examination. It is in accordance with the Decree of Indonesian National Police Number 15 of 2013 regarding Procedures for Handling Traffic Accident. Meanwhile, mediation is never used to resolve such case since there exists no legal framework. The article, therefore, suggests that revision of the Decree should be made. The criminal case resolution of traffic accidents causing death should fall into two forms, namely willful misconduct and negligence. A case with willful misconduct should be resolved through criminal justice system, while that negligence is resolved through mediation.